2011
DOI: 10.1097/qad.0b013e32834171db
|View full text |Cite
|
Sign up to set email alerts
|

Younger age at HAART initiation is associated with more rapid growth reconstitution

Abstract: Objectives Patterns of growth following highly active antiretroviral therapy (HAART) administration among children are not well defined. The objective of this study was to determine rates and predictors of growth reconstitution among children on HAART. Methods A study was conducted among HIV-1-infected children initiating HAART at an HIV treatment clinic in Kenya. Kaplan–Meier survival curves and Cox proportional hazards regression models compared catch-up growth (Z-score ≥0) at 12 months post-HAART. Multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 41 publications
5
49
1
1
Order By: Relevance
“…Children severely immunodeficient at initiation of ART may have a better growth outcome than non-immunodeficient children at initiation [32,37,41]. Other results do not prove any association between the level of immunodeficiency and nutritional recovery.…”
Section: Antiretroviral Treatment and Nutritional Status In Childrenmentioning
confidence: 84%
See 2 more Smart Citations
“…Children severely immunodeficient at initiation of ART may have a better growth outcome than non-immunodeficient children at initiation [32,37,41]. Other results do not prove any association between the level of immunodeficiency and nutritional recovery.…”
Section: Antiretroviral Treatment and Nutritional Status In Childrenmentioning
confidence: 84%
“…Nutritional problems cannot be fully explained by the effects of HIV in non-immunodeficient children, and other factors, independent of the infection, may explain why treatments are insufficient to restore the nutritional status. Furthermore, a better growth trend was observed in children with a more advanced clinical stage at ART initiation [32,37,41].…”
Section: Antiretroviral Treatment and Nutritional Status In Childrenmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, a better understanding of neurodevelopment is needed in the context of HIV infection and specific drug regimens [29]. McGrath et al found that infants on NVP-based ART demonstrated later speech attainment than those on LPV/r ART (18.1 vs 15.5 months; P = .003), although its long-term significance is yet unknown [30]. We are currently collecting longitudinal and neuropsychological assessment data among IMPAACT P1060 participants at several sites to address this gap.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have directly compared weight and height growth by calculating WHZ 24 or BMI 2,25-27 and data are therefore limited. Because children were underweight and stunted and catch-up growth in the first year of ART was particularly fast for WAZ, the degree of wasting was only moderate and normalized rapidly within 1 year.…”
Section: Discussionmentioning
confidence: 99%